Designing terahertz H-shaped dipole antenna and parametric study on the performances of the antenna / Ismail Ibrahim Edham - Ibrahim Edham, Ismail (2014)
This thesis study about the H-shaped Terahertz Dipole antenna parameters. The effect of the parameters was experimented and simulated. The designed antenna structure used copper as the patch antenna and Gallium Arsenide, GaAs as the substrate of the antenna. While there is no ground and feed line for this antenna. This is because it used laser as a feed for the antenna. The radiated wave will be radiate at the back of the antenna. The patch antenna was designed to radiate 1 THz, this frequency is just for the reference frequency as we need to do the parametric study to the parameters of the antenna. A complete simulation was done using CST Studio Suite 2013. The designed antenna are not fabricate, as it is very small in size. Only simulation was done for the designed antenna. The physical parameters that involved in this simulation are length of H-shape dipole antenna (La), width of H-shape dipole antenna (Wa), length of H-shape dipole antenna (internal length) (Ld), length of gap (L9 ), width of gap (Wg), width of substrate (l¼), length of substrate (Ls), thickness of copper (Tc) and thickness of substrate (Ts), The result obtained shows that every single physical parameters of the antenna gives unique response to the performances of the antenna. It does not have any constant response for each physical parameters. This shows that THz antenna have a lot of different from microwave antenna. The result can be used for other researcher to study about the antenna in the same scope of study.